2021
DOI: 10.1163/15685403-bja10120
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 17β-oestradiol (E2) and 17α-hydroxyprogesterone (OHP) on ovarian maturation in Penaeus semisulcatus De Haan, 1844 (Decapoda, Dendrobranchiata, Penaeidae) from the Mediterranean Sea off Alexandria, Egypt

Abstract: This study searches to provide appropriate conditions to trigger spawning in Penaeus semisulcatus in aquaculture. The aim was to test the effect of 17β-oestradiol and 17α-hydroxyprogesterone on ovarian maturation and to study the correlation between the different stages of ovarian maturation and hormonal levels in the ovaries, hepatopancreas, and haemolymph. Female shrimps were collected from Ras El-Tin beach and the fishing port to Abu Qir Bay of the Mediterranean Sea off Alexandria, Egypt from June 2018-Augu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…For example, JH can bind to Met in the nucleus and then regulate the transcription of vtg through transcription factor kr-h1 [41]. At the same time, when oocytes recognize the signal of VTG in hemolymph, steroid hormones such as JH can promote the opening of follicular cells, so that VTG can reach the surface of oocytes and combine with VGR for absorption [17,42]. In this study, we observed that in the early stage of ovarian development, there was no significant difference…”
Section: Discussionmentioning
confidence: 99%
“…For example, JH can bind to Met in the nucleus and then regulate the transcription of vtg through transcription factor kr-h1 [41]. At the same time, when oocytes recognize the signal of VTG in hemolymph, steroid hormones such as JH can promote the opening of follicular cells, so that VTG can reach the surface of oocytes and combine with VGR for absorption [17,42]. In this study, we observed that in the early stage of ovarian development, there was no significant difference…”
Section: Discussionmentioning
confidence: 99%